The alkylphospholipid edelfosine shows activity against Strongyloides venezuelensis and induces apoptosis-like cell death (2016)
Strongyloidiasis is widely distributed in the tropical and subtropical areas. Ivermectin is the drug of choice for the treatment. However, the concerns about relying treatment on a single drug make identification of new molecules a priority. Alkylphospholipid analogues, including edelfosine, are a group of synthetic compounds that have shown activity against some parasites. The objective was to assess the in vitro and in vivo activity of edelfosine, miltefosine, perifosine against Strongyloides venezuelensis. Moreover, apoptosis-like mechanism in larvae after treatment was studied. Edelfosine displayed the highest activity and the best selectivity index (LD50 = 49.6 ± 5.4 µM, SI = 1.1) compared to miltefosine or perifosine. Third stage larvae after culture with edelfosine were not able to develop an infection in mice. Treatment of mice with edelfosine showed reduction of 47% in parasitic females allocated in the gut. Moreover, DNA fragmentation was observed by TUNEL staining in larvae treated with edelfosine. These results suggest that edelfosine could be an effective drug against strongyloidiasis, probably through induction of apoptosis-like cell death. © 2016 Elsevier B.V.